Image restoration fundamentals and advances - Gunturk, Bahadir K. (Bahadir Kursat); Li, Xin, 1974- (Digital imaging and computer vision series., 2012)
Addressing a variety of applications, this book covers a wide range of topics pertaining to image restoration. Topics covered include image denoising, document image analysis, remote sensing applications, and image formation modeling. Content also addresses blind image restoration, iterative optimization techniques, learning-based image restoration, and non-local approach, as well as super-resolution, multi-spectral restoration, and video inpainting. Contributors from various countries help readers understand the essentials, the state of the art, and the research directions. The text features background material, mathematical content, a survey of the methods, examples, comparisons, and a bibliography.